Carl Rogers' Humanistic Education Concept and its Implementation in Independent Learning-Based Learning - Maida Rorano; Sahja M Aksan; Adiyana Adam; Nurmala Buamona (Manunggal Halim Jaya, 2026)
An abstract in a scientific journal should succinctly summarize the key elements of the research conducted. It should begin with a brief background that highlights the relevance or importance of the research topic. Next, the main objective or research question addressed in the study should be clearly stated. The Methods section should concisely describe the approach, techniques, and data used. The abstract should then present the key findings of the study, emphasizing significant results without excessive detail. Finally, the implications or contributions of the research to the relevant field or practice should be discussed. The entire abstract should be written in a single, coherent paragraph, avoiding overly technical terms to ensure accessibility for readers from various disciplines.